Development of integrated e-module with Live Worksheets based on PjBL with ethnomathematics nuances of typical Indonesian foods to enhance mathematical literacy - Rifan Adi Pratama; Detalia Noriza Munahefi; Angela Vivian Budianto (Universitas Sarjanawiyata Tamansiswa, 2024)
Mathematical literacy has become an essential global skill for individuals. This research aims to develop teaching modules in integrated electronic form live worksheets PjBL-based with nuances of ethnomathematics of typical Indonesian food by meeting the validity, practicality, and effectiveness criteria in increasing mathematical literacy. The research method is R&D with a model ADDIE. The population in this study was class VII students. Data collection techniques include documentary studies, unstructured interviews, observations, questionnaires, and tests. Data analysis used includes validity, practicality, and effectiveness tests. The research results show that the e-module is: (1) valid based on assessments from 3 validators on the content and presentation aspects with an average validity percentage of 88%; (2) practical based on 30 student responses with a score percentage of 84%; and (3) effective for mathematical literacy seen from individual learning completeness, classical completeness, average difference pretest, and posttest, and there is an increase in students' mathematical literacy. The result is an e-module that is valid, practical, and effective. This media can be developed more widely by adding different materials and adding various cultures in Indonesia.